Characteristics Particleboard Made From Areca Fiber With Tapioca and Gambier Adhesive - Nurdin, Hendri; Waskito, Waskito; Siregar, Batu Mahadi (Universitas Negeri Padang, 2021)
The development of engineering materials has increased its use in various fields. The engineering material is particleboard made from areca fiber which is processed with technology. Areca fiber as waste has the potential to be used as an engineering material. The purpose of this study was to obtain the characteristics of the particleboard following the quality standards of JIS A 5908-2003 and SNI 03-2105-2006. The process of making particleboard by mixing particles of areca fiber and adhesive then compacting it. The adhesives used are tapioca and gambier. The concentration of areca fiber particles is 90%, 80%, 70%, and 60%. From this research, it was found that the characteristics of the particleboard using tapioca adhesive according to the quality standard and the gambier adhesive particle board did not meet the standard quality. This particleboard can be used as a raw material for making interior furniture instead of wood.